Surface properties are highly sensitive to small ph induced changes in the 3-D structure of alpha-lactalbumin. - Gao, C; Wijesinha-Bettoni, R; Wilde, P; Mills, E; Smith, L; Mackie, A (2008)
The change in structure of bovine alpha-lactalbumin in environments of decreasing pH from pH 7 to pH 3 was followed using high-resolution NMR and hydrogen exchange studies. The effect of the changes in the structure on the surface properties of the protein was also measured. As the pH was decreased from pH 7 toward pH 2, at which alpha-lactalbumin adopts a molten globule state, a small but increasing proportion of the molecules in the sample partially unfold. There was on average a loss of tertiary structure and a change in the environment of the tryptophan residues. A significant proportion of the change measured by both circular dichroism spectroscopy and interfacial methods observed as the pH was decreased from pH 7 to pH 4 was found to be irreversible upon readjustment back to pH 7. These changes in the sample conferred an increase in surface hydrophobicity and affected the surface properties. The surface activity was found to be highest at pH 4. This was because the increasing flexibility and surface hydrophobicity of the molecule with decreasing pH was balanced by the simultaneous increase in net charge repulsion. This conclusion was also confirmed by measurements of surface shear rheology. Interestingly the interfacial dilatational rheology was highest at the isoelectric point, indicating the dominant role of the charge interaction in controlling this parameter.